Pemahaman Mahasiswa Akuntansi Terhadap Konsep Dasar Akuntansi (Studi Empiris Mahasiswa Akuntansi Kota Merauke) - Allo, Cici; Ni Luh Putu Nita Yulianti (LPPM POLITEKNIK LP3I BANDUNG, 2024)
The purpose of this study was to examine differences in students' understanding of accounting in the city of Merauke based on their educational background. Sampling through purposive sampling method. Sources of data in this study were obtained from direct interviews and literature and distributing questionnaires, namely a number of 110 Merauke City Accounting students. The data collection technique used was a five likert-scale questionnaire. The research uses SPSS data processing with different tests, hypothesis testing shows the results that H1 and H3 are accepted where the value is less than 0.05 so it can be concluded that there is a significant difference, while H2 is not accepted where the significant level is greater than 0.05. This is due to students' lack of understanding of obligations which is an important indicator in understanding the recording of financial reports. The results of the study say that there are significant differences in understanding assets and capital between students with high school and vocational educational backgrounds. There is no significant difference in understanding debt between students with high school and vocational education backgrounds.